Effect Of Motorcycles Travel Behaviour On Saturation Flow Rates At Signalized Intersections In Malaysia. - Leong, Lee Vien; Wan Ibrahim, Wan Hashim; Mohd, Ahmad Farhan (2008)

(untitled)
Mixed traffic flow with high composition of motorcycles is a common situation in most Asian countries such as Taiwan, Thailand, Vietnam and Malaysia. To date, there are approximately 7.5 million of registered motorcycles in Malaysia and motorcycle ownership in Malaysia has increased from 0.13 in year 1990 to 0.28 motorcycles per person in year 2006.